Water absorption, thickness swelling and mechanical properties of cement bonded wood composite treated with water repellent - Semiha Yılmazer; Uğur Aras; Hülya Kalaycıoğlu; Ali Temiz (Maderas: Ciencia y Tecnología)
In this study, the purpose was to improve outdoor performance of cement bonded wood composite due to their biodegradation and sensitivity to moisture especially in warm and humid climates. Cement bonded wood composites were treated with different concentrations (10 %, 25 %, 50 %, 75 % and 100 %) of water repellent. Water repellent used was an organo-silicon based, nano-sized, eco-friendly, water-based agents. Dipping and pressure systems were applied for composite treatment. Water absorption, thickness swelling, accelerated weathering, color changes and mechanical properties after accelerated weathering were determined for treated and untreated cement-bonded composites. Results showed that treatment of composites with water repellent provided a transparent layer on composite surface. Thus, lower water absorption and thickness swelling results in the beginning of immersion in water. Treated and untreated composites were exposed to an accelerated weathering test for 350 h. Their mechanical strength including modulus of rupture, modulus of elasticity and internal bonding properties were decreased after 350 h of weathering. However, overall results after weathering test showed that all panels’ mechanical properties provided minimum modulus of rupture, modulus of elasticity and internal bonding requirements of the EN standards.